Energy efficient bipedal robots walking in resonance. Issue 11 (20th May 2014) - Bauer, F.; Fidlin, A.; Seemann, W.; Fidlin, Alexander; Babitsky, Vladimir I.
Abstract This contribution presents a method to improve the energy efficiency of walking bipedal robots over 50% in a range of speed from 0.3 to 2.3 m/s by the use of constant elastic couplings. The method consists of modeling the robot as underactuated system – so that it is making use of its natural dynamics instead of fighting against it – controlling its joint‐angle trajectories with input‐output feedback linearization and optimizing the joint‐angle trajectories as well as the elastic couplings numerically. The mechanism of minimizing energy expenditure consists of reducing impact losses by choosing smaller steps, which gets favorable by a higher natural frequency due to elastic couplings. The method is applied to a planar robot with upper body, two stiff legs, two actuators in the hip joints and one simple rotational spring between the legs as elastic coupling. The mechanism of energy expenditure is investigated for the robot with and without elastic coupling between legs in detail.